OPTIMIZING NATURAL DISASTER LOCATIONS USING TEXT FILTERING WITH WEB-BASED JARO WINKLER ALGORITHM - Jatikusumo, Dwiki; Hidayat, Rahmat Rian (Informatika, Universitas Jenderal Soedirman, 2024)
At the end of 2023, several natural disasters were felt, especially in the capital city, namely floods, and the earthquake did occur outside DKI Jakarta but the earthquake was felt. From this incident, it will be made to monitor and optimize the location of earthquakes and floods that occur based on the web. According to the government website, the earthquake also occurred, but there was no flooding. Based on the occurrence of several natural disasters, it is hoped that this research can provide information related to the location of floods, earthquakes, forest fires, and landslides in the region, especially in Indonesia. With the news website source, it is the source of data that will be processed. Furthermore, the percentage level of accuracy obtained by combining from text filtering and Jaro Winkler algorithm.